Seed Dormancy and Germination - Carlos Jimenez-Lopez, Jose (IntechOpen, 2020)
Seed dormancy and germination are critical processes for the development of plants. Seed dormancy allows seeds to overcome harsh periods of seedling establishment, and is also important for plant agriculture and crop yield. Several processes are involved in the induction of dormancy and in the shift from the dormant to the germinating state, and hormones and regulatory genetic networks are among the critical factors driving these complex processes. Germination can be prevented by different factors leading to seed dormancy, which is highly dependent on environmental cues. During and after germination, early seedling growth is sustained by catabolism of stored reserves (proteins, lipids, or starch) accumulated during seed maturation, supporting cell morphogenesis, chloroplast development, and root growth until photo-auxotrophic growth can be resumed.